Factors Influencing Leprosy Incidence: A Comprehensive Analysis of Observations in Wenshan of China, Nepal, and Other Global Epidemic Areas - Li, Yu-Ye; Shakya, Sunaula; Long, Heng; Shen, Lian-Fa; Kuang, Yi-Qun (Frontiers in Public Health, 2021)
Leprosy remains endemic in some regions and is a global health concern. However, the possible causes and risk factors of the disease remain unclear. Data in Wenshan, China were collected from the Wenshan Institute of Dermatology (1986-2015); data in Nepal were obtained from the Leprosy Control Division, Department of Health Services, Nepal (2011 to 2015); and data from Indonesia, India, and Brazil were collected from WHO records. We assessed the epidemiological trends of leprosy in Wenshan and compared the features of possible causes and risk factors with those of other countries. We then performed a descriptive and statistical analysis to make our study more purposeful and definitive. A total of 3376 cases were detected in Wenshan from 1986 to 2015. The overall prevalence rate (PR) of leprosy presented a decreasing trend with a peak (4.9/10,000 population) in 1986. The detection of new leprosy cases was higher in males than in females. Visible deformity increased every year since 2005 with a disability of 34.8% in 2015 among new cases. In Nepal, 2461 leprosy patients received multi-drug therapy (MDT) in 2015 which corresponded to the PR of 0.89/10,000 population. Geographic latitude and socio-economic situations appeared to be the main causes of leprosy, and the healthcare condition was an important factor associated with leprosy incidence. The introduction of MDT effectively reduced leprosy prevalence worldwide. Wenshan (China), Nepal, and other countries share similarities in various aspects with respect to socio-cultural features, geographical distribution, environmental factors, and economic situation, which may contribute to leprosy being endemic in these areas.